Sustainable Economic Practices in Rural Indonesia: Balancing Tradition and Modernity in Post-Pandemic Era - Ahmad Maulana; Nizar Zakaria; Doni Fitriyanto (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study examines the sustainable economic transformation in rural Indonesia through a case study of Warujayeng Village, East Java, focusing on the integration of traditional practices and modern innovations in the post-pandemic era. The research addresses how rural communities navigate economic resilience by synthesizing local wisdom with technological advancements, challenging conventional modernization paradigms. Employing a qualitative approach with participatory observation, in-depth interviews, and document analysis, the study reveals three key adaptation phases: selective resistance, limited experimentation, and hybrid practice institutionalization. Findings demonstrate that 72% of traditional traders adopted digital platforms while maintaining interpersonal transactions, and polyculture farming systems showed 23% greater resilience than monocultures during crises. The study contributes to development theory by introducing